Verbal Portraits of Strong and Weak Emotional Facial Expressions - V.N. Nosulenko; A.V. Zhegallo; I.A. Basiul (Экспериментальная психология, 2024)
The article presents the results of an analysis of verbal data obtained when people compared images of emotional expressions of different intensities. The assumption is confirmed that the perceived quality of the same expression (in accordance with the categorization given in Ekman’s papers), but with different degrees of its severity, can reflect the perception of different objects. This assumption turned out to be true for both facial and affective verbal portraits - empirical referents of the perceived quality of expressions. The results obtained confirm the conclusion made in previous works that the comparison of data on the perceived quality of expressions and their list presented in Ekman’s papers is not completely legitimate, since we are not talking about the perception of the corresponding image, but about performing the task of identifying a specific expression. Accordingly, in the first case, the result is characteristics of perceived quality, in the aggregate of which the sign of a given expression will not necessarily come to the fore. In the second case, the image is assessed by the researcher himself based on data on the degree to which the subject recognizes the expression, the content of which is specified by the instructions.